Application of the generalized Clifford-Dirac algebra to the proof of the Dirac equation fermi-bose duality - Simulik, V.M; Krivsky, I. Yu; Lamer, I.L (TWMS journal of applied and engineering mathematics, 2013)
The consideration of the bosonic properties of the Dirac equation with arbitrary mass has been continued. As the necessary mathematical tool the structure and different representations of the 29-dimensional extended real Clifford-Dirac algebra (Phys. Lett. A., 2011, v.375, p.2479) are considered briefly. As a next step we use the start from the Foldy-Wouthuysen representation. On the basis of these two ideas the property of Fermi-Bose duality of the Dirac equation with nonzero mass is proved. The proof is given on the three maim examples: bosonic symmetries, bosonic solutions and bosonic conservation laws. It means that Dirac equation can describe not only the fermionic but also the bosonic states.